Characterization of engineering elastic parameters of oriented strand board (OSB) manufactured from poplar (Populus deltoides) strands using ultrasonic contact pulse transmission : Karakterizacija parametara elastičnosti ploče s orijentiranim makroiverjem (OSB) proizvedene od iverja drva topole (Populus deltoides) uz pomoć ultrazvučnoga kontaktnog prijenosa impulsa - Zahedi, Meysam (Array, 2020)
When using wood and wood-based composites, it is necessary to determine the elastic constants of these engineered materials. Oriented strand board (OSB), as structural wood based panel, plays a significant role in the building sector, but the accessibility of such elastic constants of OSB is mostly limited. For this purpose, this study aimed at determining the elastic wave velocity, stiffness and all elastic constants of OSB made from Poplar (Populus deltoides) strands using ultrasonic through–transmission technique. Laboratory OSBs with the mean density of 760 kg/m3 were made with the average strand sizes of 0.6 mm in thickness, 120 mm in length and 30 mm in width. 8 % phenol-formaldehyde (PF) resin was used with the pressing conditions of 3.43 N/mm2, 190 °C and 600 s as pressure, temperature and time of pressing, respectively. The OSBs were assumed as an orthotropic model. Three modulus of elasticity (E1, E2, and E3), three shear modulus (G12, G13 and G23), and six Poisson’s ratios (v12, v21, v13, v31, v23, v32) were calculated by longitudinal, transversal and quasi-transversal waves velocities. Ultrasonically determined stiffness coefficients of OSB were investigated by representative volume elements (RVE). Therefore, the separation of scales requirement is satisfied, and the measured velocities can be applied to determine the engineering elastic parameters of the examined OSB. The results indicate that modulus of elasticity and shear modulus are in the same order of magnitude in comparison with other references, and the values of Poisson’s ratios are valid in ultrasonic range measurement. In conclusion, the ultrasonic contact pulse transmission shows great potential to determine the characterization of elastic wave velocity, stiffness and engineering elastic parameters.